The outlook of ChatGPT, an AI-based tool adoption in Academia: applications, challenges, and opportunities - Ahadi, Navidreza; Zanjanab, Ali Ghalehban; Sorooshian, Shahryar; Monametsi, Gladness; Virutamasen, Porngarm; Wongpreedee, Kageeporn; Deebhijarn, Samart; Taghipour, Amirhossein (My University, 2023)
Artificial intelligence (AI) technologies continually improve and become more pervasive in many facets of our lives. ChatGPT is a chatbot created by OpenAI with a conversational artificial intelligence interface. Academic institutions could routinely use artificial intelligence (AI) and language models like ChatGPT, with an increasing range of applications and ramifications. This study investigates the adoption of ChatGPT in academia which include applications, challenges and opportunities using the lenses of educational transformation, response service quality, usefulness privacy concerns. The article first examine diverse applications of ChatGPT, including automation, sentiment analysis and natural language processing. Second, it addresses the challenges and limitations that come with using these technologies, like regulatory compliance algorithmic prejudice, and ethical issues. Third, the study emphasize the opportunities brought about by the implementation of AI and ChatGPT, such as improved research capacities, individualized learning experiences, and new career pathways. To promote an efficient and responsible adoption and deployment of ChatGPT, the study's findings offer several research directions and implications in academia.
Keywords: Academic Transformation; Artificial intelligence; Chatbots; ChatGPT; Conversational Agent; Higher education